Efektivitas Hukum Perlindungan Konsumen Dalam Bisnis Investasi Online - Irfan Ridha; Intan Rahmadina Putri Harahap; Abdullah Syani Alamsyah; Ahmad Sulaiman; Dea Putri Gustianingsih; Adyta Telianda; Alfani H. Mustofa; Ifthinatul Mupidah; Inayah Al-Inffah; Andre Wirandi; Dicky Kurniawan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Consumer protection in online investment businesses in Indonesia has become an important issue as cases of investment fraud increase. This study analyzes the impact of fraud on investor trust and the financial losses incurred. The QNet and MeMiles cases serve as real examples of how unrealistic profit promises can harm many individuals. Recommendations for regulatory improvements include strengthening the legal framework, enhancing the capacity of the Financial Services Authority (OJK), and promoting financial literacy. With these measures, it is hoped that a safer and more transparent investment environment can be created. This research emphasizes the importance of collaboration between authorities and the public to monitor fraudulent practices and raise awareness of investment risks. Through a comprehensive approach, Indonesia can build a more trustworthy investment ecosystem and support sustainable economic growth.